Citraan Puisi di Negeri Amplop pada MK Kajian Puisi Mahasiswa Bahasa Indonesia FKIP UNKHAIR - Nada, Anwar; Zulianto, Sugit; Wahab, Justam (STKIP PGRI SITUBONDO, 2024)
Imagery is a form of language use that can give a concrete impressions of an object, scene, action, or statement that distinguishes it from abstract expository statements and usually has something to do with symbolism. This is illustrated in the poem